The Psychometric Properties of the Norwegian version of Brown Attention-Defict Disorder Scales for Children and Adolescents, 3-7 years (Brown ADD Scales 3-7) - Bøe, Tormod; Hysing, Mari (PsykTestBarn, 2011)
Description: The Brown Attention-Deficit Disorder Scales (Brown ADD Scales) for Children aged 3- 7, developed by the clinical psychologist Dr. Thomas E. Brown, is an instrument designed to measure a broad spectrum of symptoms of impaired executive functioning related to ADD/ADHDin preschool children; i.e., impairment in the following six cognitive functions: activation, focus, effort, emotion, memory, and action. The official Norwegian translation of the Brown ADD Scales for Children aged 3-7 by Tone M. Anderssen is available through Pearson Assessments. The instrument comprises parent/caretaker-report and teacher-report forms. The instrument contains 44 items and can be completed in less than 30 minutes. Only psychologists trained in the administration and scoring of standardized tests are qualified to administer the instrument. Literature search: Our systematic literature search did not identify any studies that met theinclusion requirements. Psychometrics: None of the identified studies documented the psychometric properties of theNorwegian version of Brown ADD scales (3-7). Conclusion: The psychometric properties of the Norwegian version of the Brown ADD Scales for Children aged 3-7 have not been documented.